A health service for the nation (London : published by the Women Public Health Officers' Association)
1943-03-27 1943 1940s 8 pages A HEALTH SERVICE FOR THE NATION WITH SPECIAL REFERENCE TO PREVENTIVE SERVICES AND HEALTH EDUCATION SOME SUGGESTIONS MADE ON BEHALF OF THE WOMEN PUBLIC HEALTH OFFICERS' ASSOCIATION Founded 1896 1. The ultimate object of a National Health Service is to make available to all the possibility of complete physical and mental health. 2. This involves the provision of a healthy environment at home, at school, and at work, adequate and appropriate food, social security, freedom from strain and anxiety, adequate leisure and a wide range of interests. 3. The National Health Service must therefore concern itself with all these factors, placing the advice of those of its members who are qualified to give it at the disposal of architects, educationists, economists and others responsible for other departments of national life. It should be the responsibility of the Central Government to see that this advice is taken. 4. The National Health Service must provide for the health education of the people, who must learn that, given reasonable conditions, full health is both a possibility and a duty. This teaching is needed by children in school and by men and women, whether at home or at work. It includes the lesson of personal responsibility for obtaining and following medical and dental advice as soon as there is any loss of complete well-being. 5. The provision of this advice and of all forms of treatment is essential in any new National Health Service. This advice and treatment should be readily available to all members of the community irrespective of their economic position or of the part of the country in which they live. 292/847/2/155